SiO2-induced ferroptosis in macrophages promotes the development of pulmonary fibrosis in silicosis models. Issue 1 (8th December 2021) - Liu, Taiyang; Bao, Rui; Wang, Qiushi; Hao, Wei; Liu, Yaoyang; Chang, Sirong; Wang, Meng; Li, Yuanyuan; Liu, Zhihong; Sun, Yue
Abstract: Silicosis is a devastating disease that, without effective treatment, endangers the health of miners. Therefore, studies exploring the pathogenesis of SiO2 -induced pulmonary fibrosis are necessary to develop treatments for silicosis. Although macrophages are known to play a pivotal role in SiO2 -induced pulmonary fibrosis, the underlying mechanism remains unknown. Here, we explored whether ferroptosis was involved in SiO2 -induced pulmonary fibrosis. To this end, C57BL/6 mice and mouse macrophage (RAW264.7) cells and mouse lung fibroblast (MLF) cells were subjected to iron content, cell viability, enzyme-linked immunosorbent assay, immunofluorescence staining, histological, western blotting, quantitative reverse transcription-PCR, reactive oxygen species, and lipid peroxidation analysis. In vivo, SiO2 was found to damage the lung alveolar structure, cause infiltration of inflammatory cells, and facilitate fibrosis. Additionally, it increased the iron concentration and lipid peroxidation as well as altered the expression of ferroptosis-related genes and the mitochondrial morphology in macrophages. In vitro, ferroptosis occurred in SiO2 -treated RAW264.7 cells, which showed iron overload, lipid peroxidation, and gene alterations. Furthermore, ferrostatin-1 (Fer-1) attenuated ferroptosis in SiO2 -treated RAW264.7 cells by inhibiting lipid peroxidation and cell death and regulating ferroptosis-related genes expression, in addition to attenuating the secretion of pro-fibrotic cytokines and fibrosis. Collectively, SiO2 induces ferroptosis in macrophages, which leads to the secretion of pro-fibrotic cytokines and fibrosis.